Determination of Microbial Sensitivity to Polymyxin by the Method of Electroacoustic Analysis - O. I. Guliy; B. D. Zaytsev; A. M. Shikhabudinov; I. A. Borodina; O. S. Larionova; E. G. Zhnichkova (Антибиотики и Химиотерапия)
The influence of polymyxin on the change in the electrophysical parameters of a suspension of Escherichia coli cells of the K-12 strain was studied for the first time by electroacoustic analysis. It was shown that the maximum changes in the detected signal occur at a concentration of polymyxin of 25 μg/ml, furthermore they did not depend on the time of exposure to the antibiotic. The data obtained by the acoustic analysis method was confirmed by the standard microbiological method for determining microorganisms' sensitivity to polymyxin. The article shows the possibility of recording the sensitivity of microbial cells to antibacterial drugs and determining their antibacterial activity by the example of polymyxin with the use of the method of electroacoustic analysis of cell suspensions.